EMBERDAYAAN MASYARAKAT LUBUK MINTURUN PADANG MELALUI PENGOLAHAN JAMUR TIRAM DAN SAMPAH AN ORGANIK SEBAGAI KERAJINAN TANGAN (SENI KRIYA) - Ineng Naini; Zasmeli Suhaemi; Yusmanidar (PROSIDING: SENI, TEKNOLOGI, DAN MASYARAKAT, 2019)
The program is conducted for the activities of Field Work Experience Education and Empowerment (KKN-PPM) from students Tamansiswa University in Padang. The location called Lubuk Minturun, that located in the district of Koto Tangah Kota Padang, West Sumatra. Large of location is 8,68 km2, with a population of 6.267 people and a population density of 722/km2. People who live in Lubuk Minturun majority work as farmer. Approximately 60% of the people depend on the plantation and selling ornamental plants, they only obtained within a specified period or unpredictable incomes. Usingland yard for businesses Mushrooms and making handy craft by using an organic garbage can be a revenue opportunity toincrease people income. The method used in this activity were 4 steps: 1) socialization program, 2) training, 3) pilot project and 4) assistance, that involves 30 students. This programalso involves three groups of people in RT 1, 2 and 3 of RWX. Student which participation in this programalso trained people for processing the mushroom as nuggets and meatballs also and handy craft with various form. Based on the results of the activities can be concluded that the public response will be something new and beneficial life is very high. This is shown by the formation of three groups of people in RT 1, 2 and 3 of RWX still continued mushroom and handy craft production. Mushroom production can increased revenue of Rp 25.000 / kg andhandy craft production was Rp 100.000 until Rp. 300.000 everymonths.